(untitled) (Hematology Meeting Reports, 2009)
Transfusion with blood products containing factor VIII/VWF complex is the treatment of choice for those patients (approx. 20%) who are unresponsive to DDAVP. In developed countries, virucidally treated concentrates of FVIII/VWF complex are today the mainstay of replacement therapy in von Willebrand’s disease (VWD). The treatment indication for von Willebrand factor (VWF) concentrate in an individual patient has to be judged in the light of the severity of the disease and the type of hemostatic challenge. DDAVP can be used in many cases in connection with e.g. minor surgery, whereas concentrate should be used in major surgery. Recent data shows that the rate of biologic response to DDAVP is relatively low, not only in type 2 but also in type 1 VWD (about 1/3), when uniform and stringent criteria for patient selection and responsiveness are applied.1